PEMBERIAN MIKROORGANISME SELULOLITIK (MOS) PADA APLIKASI TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI TBM-II - TONI KASMIR LUMBANTORUAN; GUSMAWARTATI GUSMAWARTATI; SAMPERNO SAMPERNO (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
This research aimed to determine the effect of the interaction giving cellulolytic microorganisms and inorganic fertilizers or single factor to the growth of immature oil palm plantations. This research has been conducted in land PT.Tunggal Perkasa Plantation Air Molek, District Pasir Penyu, Indragiri Hulu-Riau. The research was carried out for 4 months, starting from July to October 2012. This study uses a Randomized Block Design factorial with 3 replications, the first factor is the treatment dose selulotik microorganisms composed of 4 levels (0 mL /plant, 10 mL /plant, 20 mL /plant, 30 mL /plant) and the second factor inorganic fertilizer treatment consists of 2 levels (half the recommended dose and 3/4 the recommended dose). The results showed that the interaction of cellulolytic microorganisms and low doses of inorganic fertilizers have significant effect on the increase in the number of midrib and circumference of stem. Single factor cellulolytic microorganisms giving significant effect on plant height increment, while the single factor inorganic fertilizers giving significant effect on the increase the circumference of stem and number of leaflets.